Top 10 of everything 2010 - Russell Ash (Lonfon Hamlyn, 2011)
Features hundred of separate top ten lists of statistics, anomalies, and world records of the past year, including the fastest NASCAR races, the biggest gaming publishers, the most bankable film directors, and the tallest buildings under construction.
Animal kingdom -- Mechanical creations -- Forces of nature -- Gaming -- Humankind -- Epic structures -- Sport -- Music -- Outer space -- Movies.
Includes index.
Keywords: Curiosities and wonders; World records; Popular culture; Curiosities and wonders; Popular culture; World records; Curiosities and wonders; World records; Miscellanea